Main Duct Dilatation Is the Best Predictor of High-grade Dysplasia or Invasion in Intraductal Papillary Mucinous Neoplasms of the Pancreas. Issue 6 (December 2020) - Del Chiaro, Marco; Beckman, Ross; Ateeb, Zeeshan; Orsini, Nicola; Rezaee, Neda; Manos, Lindsey; Valente, Roberto; Yuan, Chunhui; Ding, Ding; Margonis, Georgios A.; Yin, Lingdi; Cameron, John L.; et al.
Abstract : Objective: The purpose of this study is to determine preoperative factors that are predictive of malignancy in patients undergoing pancreatic resection for intraductal papillary mucinous neoplasms (IPMN). Summary Background Data: IPMN of the pancreas may be precursor lesions to pancreatic cancer (PC) and represent a target for early diagnosis or prevention. While there has been much effort to define preoperative risk factors for malignant pathology, guidelines are ever-changing and controversy remains surrounding which patients would benefit most from resection. Methods: We performed a retrospective analysis of 901 consecutive patients obtained from two tertiary referral centers who underwent pancreatic resection for histologically proven IPMN between 2004 and 2017. Collected data included patient demographic characteristics, preoperative symptoms, radiological findings, and laboratory data. Results: Main pancreatic duct (MPD) dilatation was the only variable that was significantly associated with increased probability of malignancy (defined high-dysplasia or invasion) on both univariate and multivariate analysis. Even middle-range MPD dilatation from 5 mm to 9.9 mm (n = 286) was associated with increased odds of HG-IPMN (OR = 2.74; 95% CI = 1.80–4.16) and invasion (OR = 4.42; 95% CI = 2.55–7.66). MPD dilatation >10 mm (n = 150) had even greater odds of HG-IPMN (OR = 6.57; 95% CI = 3.94–10.98) and invasion (OR = 15.07; 95% CI = 8.21–27.65). A cutoff of 5 to 7 mm MPD diameter was determined to be the best predictor to discriminate between malignant and benign lesions. Conclusions: In agreement with current IPMN management guidelines, we found MPD dilatation, even low levels from 5 mm to 9.9 mm, to be the single best predictor of HG-IPMN or invasion, highlighting the critical role that MPD plays in the selection of surgical candidates. Abstract : Supplemental Digital Content is available in the text